2014
DOI: 10.1002/ab.21532
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time hostile attribution measurement and aggression in children

Abstract: Hostile attributions are acknowledged as an important part of maladaptive social information-processing that results in aggression in children. Literature suggests the largest effect size between aggressive behavior and hostile attributions is found when hostile attributions are measured using staged situations rather than commonly used vignette-based measures (Orobio de Castro et al., 2002), but few, if any, studies have investigated hostile attributions as they occur in real-time. The current study uses an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 99 publications
(192 reference statements)
0
10
0
Order By: Relevance
“…A plausible explanation could be the lack of observations for computerized real time interactions (two effect sizes from one study), which could have resulted in an unreliable estimate of the true effect size. Another explanation could be that this study assessed computerized real‐time interactions with a presumed peer through a race‐car game (Yaros, Lochman, Rosenbaum, & Jimenex‐Camargo, ). This type of stimulus presentation might not have elicited sufficient levels of emotional engagement to evoke strong HIA, because the peer’s behavior may have been considered legitimate in the gaming context.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation could be the lack of observations for computerized real time interactions (two effect sizes from one study), which could have resulted in an unreliable estimate of the true effect size. Another explanation could be that this study assessed computerized real‐time interactions with a presumed peer through a race‐car game (Yaros, Lochman, Rosenbaum, & Jimenex‐Camargo, ). This type of stimulus presentation might not have elicited sufficient levels of emotional engagement to evoke strong HIA, because the peer’s behavior may have been considered legitimate in the gaming context.…”
Section: Discussionmentioning
confidence: 99%
“…Hare () referred to psychopathic individuals as those who were able to read others well, and, as individuals able to operate in a variety of social environments ‘conning friends and foe alike’ (p. 50). Although perspective‐taking abilities appear to be compatible with the expression of psychopathy traits (manipulation), they are not always consistent with CD (e.g., hostile attribution bias; Dodge, ; Yaros, Lochman, Rosenbaum, & Jimenez‐Camargo, ).…”
Section: Empirical Review Of External Correlatesmentioning
confidence: 99%
“…This interactive nature might enhance the experience of an actual social interaction, however it might also affect ambiguity to some extent (e.g., children who talked a lot with the virtual peer during the interaction might be prone to attribute non-hostile intent). Moreover, interactive VR is obviously costly and time-consuming to develop, and so it is relevant to directly compare this method to other assessment methods besides vignettes, such as video game tasks (e.g., Yaros et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, findings vary considerably between studies and SIP measures used. A meta-analysis (Verhoef et al, 2019) revealed that the association between aggressive behavior and children's hostile intent attributions was stronger in studies using actual social interactions (d = 1.33) than in studies using vignettes (d = 0.23 to 0.44) or video-game tasks (d = 0.36; Yaros et al, 2014). The small to moderate effect sizes for vignettes and video games may be due to a lack of emotional engagement (i.e., vignettes may not evoke strong emotions) or limited ecological validity (i.e., video games may not resemble real-life social interaction).…”
mentioning
confidence: 99%